Reconstructing Employee Green Behavior within the Framework of Organizational Positive Psychology: Theoretical Synthesis towards a Green Human Behavior Model - Linus Palindangan; Retno Kusumawati; Kuncono Yunanto; Anizar Rahayu; Retika Asih (Jurnal Psikologi, 2026)
This article aims to reconstruct Employee Green Behavior within the framework of Positive Organizational Psychology through a comprehensive qualitative synthesis of contemporary literature, with the objective of developing an integrative Green Human Behavior model. The study adopts a qualitative descriptive research design using a library study approach. Data were collected through systematic review and document analysis of recent meta analyses, systematic reviews, and conceptual studies related to employee green behavior, green human resource management, green organizational climate, and positive organizational psychology. The analytical process involved thematic identification, data reduction, conceptual categorization, and inductive interpretation to integrate fragmented theoretical perspectives. The findings indicate that Employee Green Behavior is not solely driven by cognitive motivational mechanisms such as attitudes, norms, and perceived behavioral control, but is strongly shaped by positive psychological resources including psychological capital, well being, meaning, and supportive organizational institutions. The synthesis reveals a reciprocal relationship between green behavior and employee flourishing and highlights the central role of green climate, green leadership, and green human resource management as enabling structures. Based on these findings, the article proposes a Green Human Behavior framework that integrates cognitive motivational pathways with positive psychological states and organizational contexts. This study contributes theoretically by bridging Employee Green Behavior research with Positive Organizational Psychology and practically by offering a holistic perspective for organizations seeking to advance environmental sustainability while simultaneously enhancing employee well being.